Mycobacterium Energy Metabolism as a Promising Target for Anti-TB Drugs - Kaur, Baljeet; Sharma, Savita; Chauhan, Ishita; Gupta, Monika (Current Topics in Chemistry, 2025)
The most prevalent infectious disease that affects the respiratory system is tuberculosis. The treatment for tuberculosis includes a combination of multiple antibiotics, including ethambutol, pyrazinamide, and rifampicin, which must be administered over an extended duration to effectively eliminate the mycobacteria. The main aim of the present work was to review the mechanisms and structural features of small molecules that affect mycobacterial ATP synthesis and ATP homeostasis. The mycobacteria can produce ATP in both aerobic and hypoxic environments. The enzyme ATP synthase is necessary for ATP production in both latent and developing mycobacteria. Research indicates that ATP synthase targeting small chemical compounds exhibits efficacy against latent and resistant forms of tuberculosis. The significance of mycobacterial energy metabolism as a potential target for anti-TB medications was highlighted by the FDA-approved ATP synthase inhibitor bedaquiline and a clinical candidate Q203, which interfered with the cytochrome bc1 complex of ATP synthase.
Keywords: MDR-TB